3‐(Methoxycarbonyl)Cyclobutenone as a Reactive Dienophile in Enantioselective Diels–Alder Reactions Catalyzed by Chiral Oxazaborolidinium Ions. (7th January 2021) - Yan, Peng; Zhong, Changxu; Zhang, Jie; Liu, Yu; Fang, Huayi; Lu, Ping
Abstract: Cyclobutenone has been used as a highly reactive dienophile in Diels–Alder reactions, however, no enantioselective example has been reported. We disclose herein a chiral oxazaborolidine‐aluminum bromide catalyzed enantioselective Diels–Alder reaction of 3‐alkoxycarbonyl cyclobutenone with a variety of dienes. Furthermore, a total synthesis of (−)‐kingianin F was completed for the first time via enantioenriched cycloadduct bicyclo[4.2.0]octane derivative. Abstract : The first enantioselective Diels–Alder reaction of cyclobutenone has been developed. The 3‐methoxycarbonyl group shows a remarkable effect on stability and reactivity. Based on an enantioenriched adduct, the total synthesis of (−)‐kingianin F was completed.